Experiential Learning and Change: Theory, Design, and PracticeExperiential Learning and Change: Theory, Design, and Practice, by Walter Gordon A. Marks Stephen E.. New York: John Wiley & Sons, 1981, 333 pp., $29.95 cloth. - Golembiewski, Robert T. (Academy of Management Review, 1982)
The article reviews the book “Experiential Learning and Change: Theory, Design and Practice,” by Gordon A. Walter and Stephen E. Marks.